An Analysis of Semiotic Signs in Romance Movie Posters - Darliati Darliati; Masrizal Mahmud (Universitas Syiah Kuala, 2021)
This research is a study of semiotics signs found in Indonesian romance movie posters. The subject of this research is fifteen movie posters of Indonesian romance movies. This research aims at identifying and describing the types of meaning of signs depicted in the posters based on the visual grammar theory proposed by Kress and van Leeuwen (2006). Using qualitative method, three types of meaning namely representational meaning, interactive meaning, and compositional meaning are described. The result is presented in form of written description and tables. The findings of this study show that most of the aspects of visual grammar theory can be found in the posters with every posters share different aspects. However, there are also some aspects of the visual grammar theory that are not found in the posters which are classificational process as one of sub processes of conceptual process and vertical angle in perspective aspect. Based on the depicted elements of the fifteen romance movie posters that have been analyzed, it shows that the romance movie posters involve many aspects of emotions. It includes the emotions of love, affection, hope, struggle, sadness, and desire which based on the theme of the movies. All of these emotions are presented through the colors, illumination, facial expressions of the characters, and the setting of the posters.